Femur First navigation can reduce impingement severity compared to traditional free hand total hip arthroplasty - Arnab Palit (Nature Portfolio, 2017)
Abstract Impingement is a major source of dislocation and aseptic loosening in total hip arthroplasty (THA). We compared impingement free range of motion (ROM) using a novel computer navigated femur first approach to conventional THA. In addition, impingement between genders was also explored. In a retrospective analysis of 121 THA patients, subject-specific post-operative ROM was simulated using post-operative 3D-CT data, and compared with the benchmark ROM, essential for activities of daily living. Three parameters were defined to express both implant-to-implant (ITI) and bone-to-bone (BTB) impingement - coverage percentage, third angle, and impingement severity. Although coverage percentage was similar between the navigated and conventional group for both ITI (p = 0.69) and BTB (p = 0.82) impingement, third angle was significantly reduced in the navigation group for both ITI (p = 0.02) and BTB (p = 0.05) impingement. Impingement severity for both ITI (p = 0.01) and BTB (p = 0.05) was significantly decreased in the navigation group compared to the conventional. Impingement severity in men was considerably higher compared to women for both ITI (p = 0.002) and BTB (p = 0.02). Navigation guided femur first THA is able to improve alignment of ROM axis, and consequently, to reduce impingement in THA. Men seem to be more prone to impingement than women.